A Factor Linking Floral Organ Identity and Growth Revealed by Characterization of the Tomato Mutant unfinished flower development (ufd) - Poyatos-Pertíñez, Sandra; Quinet, Muriel; Ortíz-Atienza, Ana; Yuste-Lisbona, Fernando J.; Pons, Clara; Giménez, Estela; Angosto, Trinidad; Granell, Antonio; Capel, Juan; Lozano, Rafael (Frontiers in Plant Science, 2016)
Floral organogenesis requires coordinated interactions between genes specifying floral organ identity and those regulating growth and size of developing floral organs. With the aim to isolate regulatory genes linking both developmental processes (i.e. floral organ identity and growth) in the tomato model species, a novel mutant altered in the formation of floral organs was further characterized. Under normal growth conditions, floral organ primordia of mutant plants were correctly initiated, however, they were unable to complete their development impeding the formation of mature and fertile flowers. Thus, the growth of floral buds was blocked at an early stage of development; therefore, we named this mutant as unfinished flower development (ufd). Genetic analysis performed in a segregating population of 543 plants showed that the abnormal phenotype was controlled by a single recessive mutation. Global gene expression analysis confirmed that several MADS-box genes regulating floral identity as well as other genes participating in cell division and different hormonal pathways were affected in their expression patterns in ufd mutant plants. Moreover, ufd mutant inflorescences showed higher hormone contents, particularly ethylene precursor 1-aminocyclopropane-1-carboxylic acid (ACC) and strigol compared to wild type. Such results indicate that UFD may have a key function as positive regulator of the development of floral primordia once they have been initiated in the four floral whorls. This function should be performed by affecting the expression of floral organ identity and growth genes, together with hormonal signalling pathways.